KAJIAN EPIDEMIOLOGI DAN DAMPAK SOSIAL PENYAKIT RABIES TERHADAP MASYARAKAT DI KABUPATEN MANGGARAI PERIODE 2001-2006 - Melkianus Luji-Jadi; Andrijanti H. Angi; Devi J. A. Moenek (Politeknik Pertanian Negeri Kupang, 2009)
The aims of this research are to know how about the epidemiology and social impact of rabies desease on society in Manggarai regency and to find the exact design for preventative and eliminate the rabies desease.This research was done during 8 (eight) months on March till November 2007 in Manggarai regency involved 3 districts are Langke Lembor district, Satar Mese district, and Ruteng district. Collecting primer data are information from various source such as farmer who have dogs, sacrifice of dog bite, field officer of animal husbandry department, and quarantine officers by straight interview and quisoner spreads.The result of analysis description data are total of animal (dogs) infection by rabies decreasing from 2001 (107.730) to 2006 (23.634 heads). Total of vaccination animal increase from 9.846 heads in 2001 become 13.866 heads in 2006. Total of animal elimination is decrease from 30.152 heads in 2001 become 9.861 heads in 2006.Total of dog bite were fluctuative rate from 2001 till 2006 respectly 650, 802, 652, 453, 1298 and 544 cases. Total of victims because dog bite from 2001 till 2006 were 21 heads. Result of interview for field officer of Animal Husbandry Department that effective method for preventative and eliminate rabies desease are vaccination (40-60%) and elimination of animal of rabies infector (40-60%). Spreads potential of rabies in Manggarai regency still strength and potential to spread on other regency in East Nusa Tenggara Province specially and other provincy in generally. Key word: epidemiology, social impact, rabies.